Tracer study of the employment status of Bachelor of Science in Tourism, Hotel and Travel Industry Management Graduates. - MONDIGUING, ALFREDO ISIAH A. JR. 4 0 16; 5 (2014)
ABSTRACT This preliminary tracer study determined the employment status of graduates of 2010-2012 with the degree of BS Tourism, Hotel and Travel Industry Management (BSTHTIM) of the Pamatasan ng Lungsod ng Maynila. The use of an online survey host as the primary research tool in obtaining data addressed geographic and financial constraints and increasing its accessibility and using a sampling technique by way of referral though the use of online social media. This study has focused mainly on the employment standing of these graduates and provided insights on employed graduates in the tourism industry. It revealed alternative industries graduates entered into and their entrepreneurial tendencies. This study presented current career levels indicating that most have been promoted above entry level positions and their earning capacities. The study showed that those employed in the tourism industry find the BSTHTIM program adequately prepared them in their chosen field. As a reflection of their work performance, the majority of employed have indicated their satisfaction with their current employment and have been recipients of awards and recognitions in their work place. It is strongly recommended that future researchers continue the study and provide a more in depth study on BSTHTIM graduates and involve the College of Tourism, Hotel and Travel Industry Management (CTHTIM) in a more official capacity to further increase its scope, effectiveness and utilization.
Thesis:(B.S. Travel and Tourism Management) - Pamantasan ng Lungsod ng Maynila, 2014.
Keywords: 2 -- 0; 6; 20; 20; 2